Lung recruitment in ARDS patients - Arnal, Jean-Michel; Garnero, Aude (Acta medica Lituanica, 2012)
Lung recruitment is used to improve oxygenation and decrease the risk of ventilator induced lung injuries. Assessing the potential of recruitability is a pre-requisite for a rational recruitment strategy and setting of PEEP. Using a low flow pressure-volume loop is helpful to assess the potential of recruitability at the bedside. For patients with a high potential of recruitability, recruitment maneuvers are efficient with an appropriate setting of PEEP to maintain the lung recruited. Recruitment maneuvers use pressures from 40 to 60 cmH2O for a short period of time, either with the sustained inflation or the staircase method. PEEP setting after the maneuver is important; a decreasing PEEP trial is a useful practical method.
Keywords: lung recruitment; acute respiratory distress syndrome; mechanical ventilation